Cooling and Wetting Effects of Agricultural Development on Near-Surface Atmosphere over Northeast China - Nana Zhao; Songjun Han; Di Xu; Jiandong Wang; Hongjing Yu (Advances in Meteorology)
The effects of agricultural development on observed changes in near-surface atmospheric temperature and moisture from 1960 to 2014 over Northeast China are evaluated using data from 109 meteorological stations. Cultivated land fraction (CF) within a 3 km radius of the meteorological station is used as a quantitative indicator of agricultural intensity. Stations with large CFs experience a less significant increase in air temperature, especially in daily maximum temperature (Tmax) and a more rapid increase in vapor pressure (ea) and relative humidity (RH) than stations with small CFs, especially during the main growing season (from May to September). Compared with the reference station group with CF<0.2, cooling effects during May to September in terms of daily mean, maximum, and minimum temperature by −0.067°C, −0.081°C, and −0.069°C per decade and wetting effects of May to September regarding ea by 0.075 hPa and RH by 0.56% per decade exist for the station group with CF>0.5. The cooling and wetting effects can be attributed to the agricultural development and thus should be considered when analyzing the near-surface atmospheric temperature and moisture records in Northeast China.